Antibiofilm and antibacterial effects of essential oils extracted from plants on Staphylococcus aureus - Castanha, Elisangela Ramos; Araújo, Rackel Ferreira; Falcão, Rosângela Estevão Alves; Bernardo, Vanderson Barbosa; Santana, Antônio Euzébio Goulart; Aquino, Pedro Gregório Vieira; Moreira, Keila Aparecida; Montalvo, Gualberto Segundo Agamez; Silveira Filho, Vladimir da Mota (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2023)
Staphylococcus aureus is a major pathogen among bacterial infections, also having the ability to produce biofilm, thus becoming tolerant and resistant to antibiotics and immune responses. Essential oil extracted from plants has shown broad-spectrum antibacterial and antibiofilm activities against bacteria. In this study it was evaluated whether rosemary, clove and cinnamon essential oil exert antibacterial and antibiofilm activities against S. aureus in vitro. The essential oils were purchased and their chemical composition was identified by gas chromatography and mass spectrometry (GC-MS). Antibiofilm and antibacterial effects were assessed by the 96-well microtiter plate adhesion assay. The highest antimicrobial and antibiofilm activity were observed with 3% and 6% cinnamon essential oil while the essential oil of clove and rosemary did not show satisfactory results. These results support new antimicrobial therapies against S. aureus infections and biofilm formation, using cinnamon essential oil, thus contributing to both human and veterinary medicines.